The implications of surgery on sexual dysfunction in patients with lumbar disc herniation with cauda equina syndrome: a systematic review - Zahra Moradi; Shadab Shahali; Fazlollah Ahmadi; Ali Montazeri (BMC Musculoskeletal Disorders)
Abstract Background Despite extensive literature on lumbar disc herniation and cauda equina syndrome, sexual dysfunction in these patients has been overlooked. We conducted a systematic review to gather scientific evidence on this issue following surgical treatment in this population. Methods On January 30, 2025, several databases, including PubMed, Web of Science, Scopus, and Google Scholar, were searched on the topic for English-language biomedical literature from 2014 to 2024. Two researchers assessed the quality of the articles using the Mixed Methods Appraisal Tool version 2018. The findings were narratively synthesized to effectively describe, compare, and combine the study results. Results A total of 5,893 studies were identified, but after removing duplicates and irrelevant documents, only 20 studies were eligible for analysis. Of these, 90% were rated as high quality, indicating a strong level of certainty in the evidence. The analysis revealed that the prevalence of sexual dysfunction in this population ranged from 26.6% to 100%. The most common sexual disorder among women was sexual desire and arousal disorder (35% to 60%), while erectile dysfunction was the most prevalent among men (14% to 100%). Overall, dissatisfaction with sexual activities was reported by 37% to 69% of women and 69% of men. Improvements in sexual function following surgery for lumbar disc herniation were noted in 83.33% of studies (5 out of 6), compared to only 7.14% in patients with cauda equina syndrome (1 out of 14 studies). Conclusion Studies indicated a considerable enhancement in sexual function post-surgery for lumbar disc herniation patients (68% to 99%). However, long-term follow-up of cauda equina syndrome patients revealed that many continued to experience sexual issues (14% to 100%).